2014
DOI: 10.1152/ajpheart.00839.2013
|View full text |Cite
|
Sign up to set email alerts
|

Exercise performance and peripheral vascular insufficiency improve with AMPK activation in high-fat diet-fed mice

Abstract: Intermittent claudication is a form of exercise intolerance characterized by muscle pain during walking in patients with peripheral artery disease (PAD). Endothelial cell and muscle dysfunction are thought to be important contributors to the etiology of this disease, but a lack of preclinical models that incorporate these elements and measure exercise performance as a primary end point has slowed progress in finding new treatment options for these patients. We sought to develop an animal model of peripheral va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
42
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(44 citation statements)
references
References 74 publications
0
42
0
2
Order By: Relevance
“…53 In addition, in an animal model of chronic atherosclerosis that simulated some features of PAD, a pharmacological intervention that improved exercise-induced blood flow also improved the animals' functional status. 54 The impaired vasodilation in patients with PAD is likely a sequela of the obstruction, and improvement in physiological vasodilation with exercise offers a potential therapeutic target. Microcirculatory dysfunction and local skeletal muscle flow can also be assessed by novel noninvasive imaging techniques, including arterial spin-labeling MRI and contrast-enhanced ultrasound.…”
Section: Endothelial and Microcirculatory Dysfunctionmentioning
confidence: 99%
See 1 more Smart Citation
“…53 In addition, in an animal model of chronic atherosclerosis that simulated some features of PAD, a pharmacological intervention that improved exercise-induced blood flow also improved the animals' functional status. 54 The impaired vasodilation in patients with PAD is likely a sequela of the obstruction, and improvement in physiological vasodilation with exercise offers a potential therapeutic target. Microcirculatory dysfunction and local skeletal muscle flow can also be assessed by novel noninvasive imaging techniques, including arterial spin-labeling MRI and contrast-enhanced ultrasound.…”
Section: Endothelial and Microcirculatory Dysfunctionmentioning
confidence: 99%
“…The indirect 5′ AMP-activated protein kinase activator R118 has improved exercise performance and vascular insufficiency in high-fat fed mice. 54 Although the overlapping metabolic functions of ERRα and ERRγ suggest potential benefit for patients with PAD, breast cancer association studies suggest that ERRα and ERRγ have differing effects on cancer progression, with high levels of ERRα associated with expression of ErbB2, increased risk of recurrence, and adverse clinical outcomes. 161,162 Thus, careful choices of pharmacological agents will need to be made if mitochondrial biogenesis in patients with PAD will be attempted through ERR modulation.…”
Section: Skeletal Muscle Metabolic Abnormalitiesmentioning
confidence: 99%
“…Therefore, based on the strong preclinical and emerging clinical evidence with this compound there are excellent reasons to pursue more potent and efficacious complex I inhibitors that activate AMPK via this mechanism. Recently, several molecules that fit this description have been described (125, 126) but to date none of them have been tested in preclinical models or even on DRG or TG neurons. One potential reason to favor complex I inhibitors versus other mechanisms of action for regulating AMPK is the emerging evidence for mitochondrial dysfunction in several forms of neuropathic pain (91, 127).…”
Section: Developing Novel Therapeutics For Pain Targeting Ampkmentioning
confidence: 99%
“…We previously confirmed that PMFs, particularly 5,7-dimethoxyflavone in KPE, improved metabolism in muscle cells by activating AMPK [24]. AMPK is known to play a critical role in the regulation of energy homeostasis and is related to physical fitness, endurance, and fatigue [41][42][43][44][45][46][47][48]. For example, 5-aminoimidazole-4-carboxyamide ribonucleotide (AICAR), an AMPK agonist, was reported to increase running endurance by 44% and decrease body fat in mice following its oral administration for 4 weeks [48].…”
Section: Discussionmentioning
confidence: 89%